2014
DOI: 10.1111/geb.12253
|View full text |Cite
|
Sign up to set email alerts
|

Foliar elemental composition of European forest tree species associated with evolutionary traits and present environmental and competitive conditions

Abstract: 44In the same genus co-occuring species had overall higher differences in foliar 45 elemental composition and stoichiometry than the non co-occuring species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 37 publications
4
101
1
1
Order By: Relevance
“…This standard functional leaf ionome can be determined from surveys of the leaf ionomes of a representative selection of angiosperms grown under nutrient‐replete conditions. This might be achieved by sampling species from their natural habitats (Reich and Oleksyn , Watanabe et al , Fyllas et al , Zhang et al , White et al , Cornwell et al , Hao et al , Hayes et al , Sardans et al , He et al , Verboom et al ) or by growing species in controlled environments (Broadley et al , , White et al , ). Each of these approaches offers advantages and disadvantages.…”
Section: The Functional Ionomementioning
confidence: 99%
See 1 more Smart Citation
“…This standard functional leaf ionome can be determined from surveys of the leaf ionomes of a representative selection of angiosperms grown under nutrient‐replete conditions. This might be achieved by sampling species from their natural habitats (Reich and Oleksyn , Watanabe et al , Fyllas et al , Zhang et al , White et al , Cornwell et al , Hao et al , Hayes et al , Sardans et al , He et al , Verboom et al ) or by growing species in controlled environments (Broadley et al , , White et al , ). Each of these approaches offers advantages and disadvantages.…”
Section: The Functional Ionomementioning
confidence: 99%
“…In general, plant species from the same family grown in the same environment have similar leaf ionomes, whereas those of different families and orders are distinct (Broadley et al , White et al ). Furthermore, despite the effects of environment on the leaf ionome, strong phylogenetic effects on the mineral composition of plant species can still be observed even in extensive field surveys (Garten , Thompson et al , Kerkhoff et al , Watanabe et al , Fyllas et al , Metali et al , Zhang et al , Cornwell et al , Hao et al , Viani et al , Sardans et al , He et al , Verboom et al ), surveys of plots receiving contrasting fertilisation, such as the Rothamsted Park Grass Experiment (White et al ), and pot experiments with contrasting soils (Viani et al , Quintero‐Vallejo et al ). For example, the leaves of Poales are characterised by relatively small Ca, Mg and B concentrations, leaves of Brassicales are characterised by relatively large Ca, Zn and S concentrations, and leaves of Caryophyllales are characterised by relatively large Mg, Zn and Na concentrations (Fig.…”
Section: Phylogenetic Effects On the Leaf Ionomementioning
confidence: 99%
“…α < 1.0) [1]. The large-scale patterns of the leaf N and P stoichiometry in relation to environmental conditions (especially temperature), biogeochemical gradients, intrinsic genetic factors and species composition have been generalized in previous studies [10][11][12][17][18][19]. Moreover, a constant exponent of leaf N vs. P scaling is appealing to, and chased by, ecologists for its simplicity in model operations.…”
Section: Introductionmentioning
confidence: 99%
“…Sönke Zaehle reported that current C–N models, in contrast to measurements in Free Air CO 2 Enrichment (FACE) experiments, achieve a positive response in net primary productivity (NPP) primarily by increasing C : N at the tissue level (Zaehle et al ., ); however, the models fail to reproduce the observed shift towards belowground C allocation and increased N uptake. Ivan Janssens reported that leaf N concentrations across European forests is co‐determined by phylogeny and, while spatial differences in stoichiometry within plant species can be large, temporal responses to environmental change appear small (Sardans et al ., ). It became clear that stoichiometric flexibility in different plant tissues and leaf‐level photosynthetic capacity – as well as their response to changes in atmospheric CO 2 and soil nutrient availability – warrant special attention from empiricists, as well as in the formulation of models.…”
Section: Nitrogen Constraints On Plant Co2 Responsesmentioning
confidence: 97%